PERAN OPPORTUNITY ENTREPRENEUR DALAM PERTUMBUHAN EKONOMI - Kurniasari, Dian (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
Not all entrepreneurs demonstrate the same kind of behaviors. An‘opportunity’ entrepreneur starts a new business by exploiting anidentifiable business opportunity and is expected to help develop theeconomy. On the other hand, a ‘necessity’ entrepreneur does so in order tosurvive over poverty and/or unemployment, and thus can hardlycontribute much to the economic development. This paper to describesthis types of entrepreneur.